Design and Manufacture of 6 Axis Force and Moments Transducers for Seaplane Floaters Test in Towing Tank - Nurhadi Nurhadi; Mochammad Nasir; Chandra Permana; Endah Suwarni (EPI International Journal of Engineering, 2020)
To develop seaplanes as a means of inter-island transportation, it is necessary to have a simulation, testing, and analysis of force measurements that work so that the aircraft can be designed optimally in terms of function and safety. To fulfill one type of test, the seaplane floater model is pulled in the Towing Tank to determine the hydrodynamic forces acting on the floater which include resistance (Fx), side force (Fy), lift force (Fz), and moments in all three axes. A method of measuring the force of 6 axis force and moment or 6 degrees of freedom (6 Degree of Freedom, 6 DOF) was built and designed by combining several single load cells so that these forces can be known optimally. From the results of the 6 DOF transducer design, it is proven that it can be used well in measuring 6 forces and moments with force measurement errors ranging from 1.38%. The distance between the 6 DOF transducer capture point and the floater force capture point will affect the measured moment transformation.